Predictors of poor glycaemic control among type two diabetic patients - Al-Mutairi, Mansour A.; Md Said, Salmiah; Zainuddin, Huda (Scientific & Academic Publishing, 2013)
Diabetes is the sixth leading cause of death and results in high morbidity[1]. In Saudi Arabia, diabetes affected 24.7% of the population and cost 51 Billion Saudi Riyal for treatment[10]. Furthermore, the prevalence of poor physical activity and obesity was high in Saudi Arabia which was 96.1% and 35.5% respectively[11, 12]. However, it is very limited information on obesity, physical activity and glycemic control in Saudi. Since, diabetes management includes not only pharmacotherapy but also modification of lifestyles, thus, this study is conducted to determine which factors, including obesity, level of physical activity, dietary intake and socio-demographic characteristics are associated with poor glycemic control among type two diabetic patients in the Almadinah Diabetic Centre. Study showed that the proportion of adult in the U.S. with adequately glycemic controlled decreased between 1988 and 2000 from 44.5% to 35.8%[9]. The predictors of Poor glycemic control can be determined to be age above 40 years old, poor diet, lack of participation in regular physical activities, oral treatment and combination therapies with oral and diet, low income, lack of knowledge and education on the issue, obesity and duration of diabetes.